Bound States in the Continuum in Anisotropic Plasmonic Metasurfaces - Liang, Yao; Koshelev, Kirill; Zhang, Fengchun; Lin, Han; Lin, Shirong; Wu, Jiayang; Jia, Baohua; Kivshar, Yuri (Nano letters, 2020)
The concept of optical bound states in the continuum (BICs) currently drives the field of dielectric resonant nanophotonics, providing an important physical mechanism for engineering high-quality (high-Q) optical resonances in high-index dielectric nanoparticles and structured dielectric metasurfaces. For structured metallic metasurfaces, realization of BICs remains a challenge associated with strong dissipative losses of plasmonic materials. Here, we suggest and realize experimentally anisotropic plasmonic metasurfaces supporting high-Q resonances governed by quasi-BIC collective resonant modes. Our metasurfaces are composed of arrays of vertically oriented double-pillar meta-molecules covered by a thin layer of gold. We engineer quasi-BIC modes and observe experimentally sharp resonances in mid-IR reflectance spectra. Our work suggests a direct route to boost the resonant field enhancement in plasmonic metasurfaces via combining a small effective mode volume of plasmonic systems with engineered high-Q resonances provided by the BIC physics, with multiple applications to enhance light-matter interaction for nano-optics and quantum photonics.